1987
DOI: 10.1172/jci113224
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective effects of glycine and glutathione against hypoxic injury to renal tubules.

Abstract: Roles for both the tripeptide, GSH, and individual amino acids in modifying the cellular response to oxygen deprivation-induced injury have been suggested by prior work in kidney and other tissues, but the precise interrelationships have not been clearly defined. We have studied the effects of GSH, its component amino acids, and related compounds on the behavior of isolated renal proximal tubules in a well characterized model of hypoxic injury in vitro. GSH, the combination of cysteine, glutamate, and glycine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
141
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(156 citation statements)
references
References 53 publications
14
141
1
Order By: Relevance
“…28,32,33 Tubules were suspended at 3.0 to 5.0 mg of tubule protein/ml in a 95% O 2 /5% CO 2 5.0 sodium butyrate, 3% dialyzed dextran (T-40, Pharmacia), and 2 glycine. Medium A was also supplemented with 0.5 mg/ml of bovine gelatin (75 bloom) to suppress aggregation of the isolated tubules during the prolonged experimental incubation periods.…”
Section: Isolation Of Tubulesmentioning
confidence: 99%
See 2 more Smart Citations
“…28,32,33 Tubules were suspended at 3.0 to 5.0 mg of tubule protein/ml in a 95% O 2 /5% CO 2 5.0 sodium butyrate, 3% dialyzed dextran (T-40, Pharmacia), and 2 glycine. Medium A was also supplemented with 0.5 mg/ml of bovine gelatin (75 bloom) to suppress aggregation of the isolated tubules during the prolonged experimental incubation periods.…”
Section: Isolation Of Tubulesmentioning
confidence: 99%
“…This situation has improved with recognition that much of their sensitivity is because of the formation of pathological plasma membrane pores that can be blocked by glycine at physiological levels. 28,29 By suppressing this type of plasma membrane damage, replacement of glycine allows examination of specific injury mechanisms in vitro, uncomplicated by the plethora of postmortem degenerative changes that would otherwise occur in multiple cellular systems. 30 -32 We have found that, despite glycine cytoprotection, freshly isolated, kidney proximal tubule cells develop a profound …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations have indicated that the amino acid content of the suspension solution may have profound effects on the stability of a suspension of tubules and the severity of an injury to renal tubules (4,5). Moreover, the common buffer solutions used for tubules from mature rats are different from those used for immature tubules.…”
mentioning
confidence: 99%
“…The standard buffered Ringer's solution used to study adult tubules contains lactate. alanine, and butyrate (5,6), and glutamine and malate are frequently added in studies of immature tubules (7). Therefore, we studied the stability of both mature and immature tubules in three buffer solutions.…”
mentioning
confidence: 99%